Autologous Minimally Invasive Cell-Based Therapy for Meniscal and Anterior Cruciate Ligament Regeneration - Pradeep V. Mahajan; Swetha Subramanian; Siddhesh C. Parab; Sanskruti Mahajan (Case Reports in Orthopedics)
The meniscus is a fibrocartilaginous tissue that acts as a “shock absorber,” along with performing functions such as stabilization and lubrication of the joint, proprioception, and load distribution. Sudden twisting movements during weight bearing or trauma can cause injury to the menisci, which leads to symptoms such as pain, swelling, and difficulty in performing movements, among others. Conventional pharmacological and surgical treatments are effective in treating the condition; however, do not result in regeneration of healthy tissues. In this report, we highlight the role of cell-based therapy in the management of medial and lateral meniscal and anterior cruciate ligament tears in a patient who was unwilling to undergo surgical treatment. We injected autologous mesenchymal stem cells obtained from the bone marrow and adipose tissue and platelet-rich plasma into the joint of the patient at the area of injury, as well as intravenously. The results of our study corroborate with those previously reported in the literature regarding the improvement in clinical parameters and regeneration of meniscal tissue and ligament. Thus, based on previous literature and improvements noticed in our patient, cell-based therapy can be considered a safe and effective therapeutic modality in the treatment of meniscal tears and cruciate ligament injury.